ted has $550 saved. he also received a grant for $2,500 and a scholarship for $1,000. he will take out student loans for the rest of the cost. then ted will take out in student loans this year is $2700
Tuition at valley view community college amount $6,750 this year.
ted has $550 saved.
he also received a grant for $2,500
and a scholarship for $1,000.
he will take out student loans for the rest of the cost.
how much money will ted take out in student loans this year?
Total amount ted have
=550+2500+1000
= 4050
but ted have to pay college amount =6750
ted take out in student loan = 6750 -4050
= 2700
ted take out in student loans this year is $ 2700
learn more about of amount here
brainly.com/question/13024617
#SPJ4
Answer:
![4(x^{2} -4)^{2} -76](https://tex.z-dn.net/?f=4%28x%5E%7B2%7D%20-4%29%5E%7B2%7D%20-76)
Step-by-step explanation:
Take out 4:
4(x^2-8x)-12
=4(x^2-8x+16-16)-12
=4(x^2-8x+16)-64-12
=4(x^2-4)^2 - 76
=![4(x^{2} -4)^{2} -76](https://tex.z-dn.net/?f=4%28x%5E%7B2%7D%20-4%29%5E%7B2%7D%20-76)
Answer:
a = 4,
b = 12
c = 10
d = 15
Step-by-step explanation:
Since the product of each column is equal, therefore,
b*5 = 60
b = 60 ÷ 5 = 12
c*6 = 60
c = 60 ÷ 6 = 10
Since the sum of each column are equal, therefore,
12 + 10 + a = 5 + 6 + d
22 + a = 11 + d
Think of a number you can add to 22, and another number you can add to 11, which will make both sides equal. Add both numbers, whenmultiplied together should give you 60.
Factors of 60 are:
(a, d)
(1, 60) => 22 + a = 11 + d => 22+1 = 11+60 (incorrect)
(2, 30) => 22 + a = 11 + d => 22+2 = 11+30 (incorrect)
(3, 20) => 22 + a = 11 + d => 22+3 = 21+20 (incorrect)
(4, 15) => 22 + a = 11 + d => 22+4 = 11+15 => 26 = 26 [CORRECT]
(5, 12) => 22 + a = 11 + d => 22+5 = 11+12 (incorrect)
(6, 10) => 22 + a = 11 + d => 22+6 = 11+10 (incorrect)
Therefore,
a = 4,
d = 15
1/2 ÷10=1/20 because you multiply the bottoms
3÷1/6= 18 because it is the same as 3×6
1/4 + 1/2 + x = −3/4
get a common denominator 1/4
1/4 +2/4 +x = -3/4
combine like terms
3/4 +x =-3/4
subtract 3/4 from each side
x = -3/4 -3/4
x = -6/4
divide top and bottom by 2
x = -3/2
x = -1 1/2
Answer : x = -1 1/2